The mediating role of job satisfaction between psychological capital and work engagement among Chinese nurses during COVID-19 outbreak: A comparative study between nurse specialists and general nurses - Zhang, Minyi; Chen, Hongyu; Wang, Ning; Li, Yao; Li, Xiaofei; Liu, Yan (Frontiers in Psychiatry, 2023)
Background The outbreak of COVID-19 has become a global public health emergency, causing great psychological distress to nurses. It is unknown whether the pandemic will affect the work engagement of nurses, the relationship between psychological capital, job satisfaction, and work engagement among nurses, and whether there are differences between nurse specialists and general nurses during the pandemic. Objectives The purpose of this study was to compare psychological capital, job satisfaction, and work engagement among nurse specialists and general nurses during the pandemic, as well as to test the role of job satisfaction as a mediator in the association between psychological capital and work engagement among nurses, and to examine whether the underlying mechanism of the relationship between psychological capital and job satisfaction differs between nurse specialists and general nurses. Materials and methods A convenience sampling was used to assess a sample of 372 nurse specialists and 318 general nurses from nine provincial general hospitals in China to participate in the online survey. Data were collected using self-report questionnaires, including the following tools: self-designed socio-demographic questionnaire, psychological capital scale, job satisfaction scale, and work engagement scale. Results Compared with general nurses, the nurse specialists had higher psychological capital, job satisfaction, and work engagement. Job satisfaction partially mediated the positive association between psychological capital and work engagement and the indirect effect was stronger in nurse specialists in comparison to general nurses during the COVID-19 pandemic. Conclusion The findings provide important practical implications for future intervention programs aimed at enhancing nurses’ work engagement, which may be realized through strengthening psychological capital and job satisfaction during the pandemic. Moreover, considering the cost-effectiveness of limited health care spending, nursing managers should pay more attention to the continuing professional development of young general nurses.